Bamboo Violin Innovation in Japan Village Kudus Regency (Universitas Negeri Semarang, 2023)
The violin is a common musical instrument constructed of wood, specifically a variety of maple wood. A bamboo violin musical instrument has been created by a woodworker from Kudus Regency's Japan Village. The aim of this study was to discover and describe the innovations used by woodworkers in the production of violins in Japan Village, Kudus Regency, as well as the discovery and description of the production method for bamboo-based violins in Japan Village, Kudus Regency. The research was conducted using a case study research design and a qualitative research methodology. Following are the study's findings: 1) Local wood and bamboo, such as petung bamboo, rosewood wood, Dutch teak wood, and wood mahogany, are used as the basic building blocks for violins. Wood craftsmen also incorporate Indonesian wayang carvings and a scroll design with an eagle head and a puppet head that both have symbolic meaning when creating violin designs for their musical instruments.